Regulation of ubiquitination in sepsis: from PAMP versus DAMP to peripheral inflammation and cell death - Li, Yueying; Yu, Jiongyan; Zeng, Zhiwen; Lin, Weixiong (Frontiers in Immunology, 2024)
Sepsis (sepsis) is a systemic inflammatory response triggered by infection, and its pathologic features include overproduction of peripheral inflammatory factors (e.g., IL-1β, IL-6, TNF-α), which ultimately leads to cytokine storm and multiple organ dysfunction syndrome (MODS). Pathogen-associated molecular patterns (PAMP) and damage-associated molecular patterns (DAMP) induce strong immune responses and exacerbate inflammation by activating pattern recognition receptors (PRRs) in the host. Ubiquitination, as a key protein post-translational modification, dynamically regulates the activity of several inflammation-associated proteins (e.g., RIPK1, NLRP3) through the coordinated action of the E1, E2, and E3 enzymes, affects cell death pathways such as necroptosis and pyroptosis, and ultimately regulates the release of peripheral inflammatory factors. Deubiquitinating enzymes (DUBs), on the other hand, influence the intensity of the inflammatory response in sepsis by counter-regulating the ubiquitination process and balancing pro- and anti-inflammatory signals. This review focuses on how PAMP and DAMP activate inflammatory pathways via PRRs, and the central role of ubiquitination and deubiquitination in the development of sepsis, especially the mechanisms in regulating the secretion of peripheral inflammatory factors and cell death. By deeply dissecting the impact of the balance of ubiquitination and deubiquitination on inflammatory regulation, we further envision its potential as a therapeutic target in sepsis.